Pengaruh Fungsi Mentoring dan Partisipasi Dalam Penetapan Tujuan Terhadap Kualitas Hubungan Supervisor-Auditor: Peran Keadilan Organisasi Sebagai Variabel Mediasi - - Rispantyo; - Rahmawati (Conference In Business, Accounting, And Management (CBAM), 2012)
Mentoring in the Badan Pengawasan Keuangan dan Pembangunan (BPKP) is an important program in an effort to carry out its role supporting the accountability of the President through the Capacity Building, Current Issues, Clearing House, and Check and Balance. Drawing on goal setting, socialization, and organizational justice theories, a model of the mediating role of organizational justice perceptions was developed and tested with path analysis. This paper investigates the perceptions of distributive and procedural justice as a mediation between the effects of mentoring fuctions and participation in goal setting on quality of supervisor-auditor relationship. The sample included 41 government auditor in BPKP Daerah Istimewa Yogyakarta (DIY). The analysis showed that distributive justice as a mediation between the effect of mentoring function on quality of supervisor-auditor relationship, but not for procedural justice. The results of this study also found evidence that distributive justice as a mediation between the effect of participation in goal setting on quality of supervisor-auditor relationship, but not for procedural justice. The paper finds that if mentoring goes well, it is directly or indirectly to improve the quality of supervisor- auditor relationship, through distributive justice. The paper includes implications for developing effective mentoring programs for government auditor.Key words: Â Â Â mentoring, goal setting, ditributive justice, procedural justice, supervisor-auditor relationships.